Nutritional quality of snacks commercialized in Portugal - Albuquerque, T.G. (2016)
Objective: To evaluate nutritional quality of 22 snacks available in Portugal, considering its total fat, salt and fatty acids profile. Moreover, commercial and supermarket brands of each product were compared to assess a possible effect of price on the nutritional quality of foods. Methods: Twenty two samples of snacks (cream crackers, popcorns, cheese snacks and salty biscuits) were acquired in supermarkets. Total fat determination was performed by acid hydrolysis method followed by Soxhlet’s extraction with petroleum ether. The salt content was determined by Charpentier Volhard’s titration. Fatty acids methyl esters were analyzed using gas chromatography coupled with flame ionization detection. Results: Snacks have high total fat contents, varying between 3.67 ± 0.0 and 36.7 ± 0.8 g/100 g of edible portion. With respect to salt content, the values ranged from 0.0465 ± 0.0 (popcorn) to 4.49 ± 0.1 g/100 g (salty biscuit). In our study, the most abundant fatty acids in the analysed samples were palmitic acid (C16:0) and oleic acid (C18:1). Considerable differences in total fat and salt contents were found between commercial and supermarket brands. Conclusions: This study demonstrated that snacks commercialized in Portugal can greatly contribute for the intake of fat, salt and saturated fatty acids.